PENERAPAN MODEL PEMBELAJARAN KOOPERATIFE TIPE TALKING STICK UNUK MENINGKATKAN HASIL BELAJAR IPS KELAS V SD NEGERI 002 USUL KECAMAAN BATANG GANSAL KABUPATEN INDRAGIRI HULU - Asnita, Asnita; Alpusari, Mahmud; Daud, Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrac: The problem of this research in learning IPS have impact that’s not active, the process teaching and learning that implemented in classroom opten exprience the faiture that’s not apprapriate based on the problem .so that need to look for the solution to solve the problem. One of to solve the problem by applying the learning model talking stick to improve the result of the learning students class V SDN 002 Usul 0f academic year 2014-2015 with the number of students 32 people. This research doing in two cycles two mectings and one meoting daily best. The intrument of the data collection this research inform action research classroom (PTK) ains to improve the result of the learning students class V SDN 002 Usul in material proklamation of independence. The result of this research show that the learning model talking stick can improve the result of the learning, can see from an increase in the base score with average 62,82 in cycle increase with everage 65,29 meanwhite in second cykle increased to 80,65. Based on the result that obtainned in this research just taken rating coognitive can conclude that the learning application by using learning model cooperative type talking stick can improve aktivity and the result of learning students in learning IPS espectally students class V SDN 002 Usul Kecamatan Batang Gansal , Kabupaten Indragiri Hulu.Keyword : Learning Model Cooperative Type Talking Stick